The Future of Electric Cars in Indonesia: Exploring Factors Influencing The Purchase Intention Through The Modified Theory of Planned Behavior - Irwanda Kurniawan; Laurentia Hutauruk; Yulianto Wahyu Putra; Synthia Atas Sari (Green Publisher Indonesia, 2025)
This study explores the factors influencing the purchase intention of electric cars in Indonesia using a modified approach to the Theory of Planned Behavior (TPB). With increasing air pollution caused by fossil-fuel vehicles, Electric Cars (ECs) have emerged as an environmentally friendly solution. However, challenges such as limited charging infrastructure and relatively high prices hinder their adoption in Indonesia. The study employs a survey-based questionnaire with respondents who have knowledge about electric cars. The analysis incorporates factors such as brand knowledge, environmental concern, perceived risk, and price sensitivity. The results indicate that brand knowledge and environmental concern positively influence attitudes, which in turn affect purchase intention. Subjective norms and perceived behavioral control also play significant roles in shaping purchase intentions. On the other hand, perceived risk negatively impacts purchase intention, while price sensitivity does not significantly moderate the relationship between attitude and purchase intention. This research provides practical implications for automotive companies and policymakers to promote the adoption of electric cars in Indonesia by improving infrastructure and educating the public on the environmental benefits and long-term cost efficiency of electric vehicles.